PERCEPTION OF MOTHERS ABOUT PNEUMONIA - Kundi, M.Z. Malik; Anjum, M.; Siddique, M. N. (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT 57 randomly selected mothers were assessed for their perception about pneumonia by showing them children with severe pneumonia. The abnormal signs shown were recognised by all of them. Nearly 50% of them related these signs with '˜pneumonia'. The results indicate that flaring alae nasi is the sign which mothers find easiest to spot.